2010
DOI: 10.1002/jnr.22442
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone regulates the phosphorylation of protein phosphatases in the brain

Abstract: Previous studies have shown that progesterone modulates the activity of different kinases and the phosphorylation of Tau in the brain. These actions of progesterone may be involved in the hormonal regulation of neuronal differentiation, neuronal function, and neuroprotection. However, the action of progesterone on protein phosphatases in the nervous system has not been explored previously. In this study we have assessed the effect of the administration of progesterone to adult ovariectomized rats on protein ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…The actions of PROG during physiological conditions involve the regulation of the activity of different kinases and phosphatases (Amorim et al, 2010;Frye and Walf, 2008;Guerra-Araiza et al, 2007Mani and Oyola, 2012) and the activation of membrane and intracellular progesterone receptors Mani and Oyola, 2012;Meffre et al, 2013). PROG and its metabolite DHP bind to intracellular PROG receptors , which are expressed in the nervous system (Guerra-Araiza et al, 2003).…”
Section: Physiological Actions Of Progesterone and Its Metabolites Inmentioning
confidence: 99%
“…The actions of PROG during physiological conditions involve the regulation of the activity of different kinases and phosphatases (Amorim et al, 2010;Frye and Walf, 2008;Guerra-Araiza et al, 2007Mani and Oyola, 2012) and the activation of membrane and intracellular progesterone receptors Mani and Oyola, 2012;Meffre et al, 2013). PROG and its metabolite DHP bind to intracellular PROG receptors , which are expressed in the nervous system (Guerra-Araiza et al, 2003).…”
Section: Physiological Actions Of Progesterone and Its Metabolites Inmentioning
confidence: 99%
“…Recently it has been reported that, in rat brain, progesterone regulates the expression of Phosphatase and Tensin homolog deleted on chromosome TEN (PTEN) gene . PTEN acts as a tumour suppressor by dephosphorylating the plasma membrane lipid second messenger phosphoinositide‐3,4,5‐trisphosphate (PIP3) antagonizing signal transduction downstream of phosphatidylinositol‐3 kinase (PI3K) and suppressing cell growth and survival .…”
Section: Introductionmentioning
confidence: 99%
“…Nongenomic effects of progesterone on DRG neurons include potentiating P2X2 receptors 88 . Progesterone also regulates activity of kinases and phosphatases, 89 and activates MAP kinases including ERK 90 . Little is known about potential effects of progesterone on central or peripheral trigeminal neurons, or about how estrogen and progesterone may interact to regulate ERK activation.…”
mentioning
confidence: 99%